Forensic electrochemistry: indirect electrochemical sensing of the components of the new psychoactive substance Synthacaine - Cumba, Loanda Raquel [UNESP]; Kolliopoulos, Athanasios V.; Smith, Jamie P.; Thompson, Paul D.; Evans, Peter R.; Sutcliffe, Oliver B.; Carmo, Devaney Ribeiro do [UNESP]; Banks, Craig E. (Royal Society of Chemistry (RSC), 2015)
Synthacaine is a New Psychoactive Substance which is, due to its inherent psychoactive properties, reported to imitate the effects of cocaine and is therefore consequently branded as legal cocaine. The only analytical approach reported to date for the sensing of Synthacaine is mass spectrometry. In this paper, we explore and evaluate a range of potential analytical techniques for its quantification and potential use in the field screening Synthacaine using Raman spectroscopy, presumptive (colour) testing, High Performance Liquid Chromatography (HPLC) and electrochemistry. HPLC analysis of street samples reveals that Synthacaine comprises a mixture of methiopropamine (MPA) and 2-aminoindane (2-AI). Raman spectroscopy and presumptive (colour) tests, the Marquis, Mandelin, Simon's and Robadope test, are evaluated towards a potential in-the-field screening approach but are found to not be able to discriminate between the two when they are both present in the same sample, as is the case in the real street samples. We report for the first time a novel indirect electrochemical protocol for the sensing of MPA and 2-AI which is independently validated in street samples with HPLC. This novel electrochemical approach based upon one-shot disposable cost effective screen-printed graphite macroelectrodes holds potential for in-the-field screening for Synthacaine.